A rapid, non-invasive population assessment technique for marine burrowing macrofauna inhabiting soft sediments. (31st October 2019) - Campbell, Lily; Wood, Lisa; Allen Gerwing, Alyssa M.; Allen, Shaun; Sizmur, Tom; Rogers, Megan; Gray, Olivia; Drewes, Mitch; Juanes, Francis; Gerwing, Travis G.
Abstract: Population assessment techniques for soft-sediment infauna (invertebrates within the substrate) requires excavation of specimens, damaging or killing the specimen and surrounding habitat, while being time-consuming and costly. Rapid population assessments of some marine burrowing decapods have been possible by counting burrow openings to estimate abundance, and while they may be used as indicator species, these decapods are not ubiquitous to environments requiring monitoring. Additionally, the presence of other burrowing macrofauna (invertebrates living in the sediment and retained on 1 mm mesh such as clams or large worms) may reduce the efficacy of burrow openings in estimating macrofauna abundance. As such, we assessed mudflats along the north coast of British Columbia, Canada, during summer 2017 to determine if macrofauna abundances could be estimated from burrow openings on the sediment surface in regions of low (n = 1 species) and high (n = 8 species) biodiversity. Abundance could not be estimated at the low diversity sites where only one macrofaunal species created burrows. At the high diversity site, species-specific models estimating abundance from burrow openings could not be constructed; however, the total number of burrow openings observed was useful in estimating total infaunal community abundance. As such, burrow openings may not be an effective tool in assessing species-specific abundances, but may be appropriate to estimate overall community changes.